Aryl-alkyl-lysines: small molecular membrane-active antiplasmodial agents12. Issue 2 (12th January 2017) - Ghosh, Chandradhish; Chaubey, Shweta; Tatu, Utpal; Haldar, Jayanta
Abstract : Water-soluble membrane-active compounds, that are active against Plasmodium sp. both in vitro and in vivo are reported. Abstract : Due to emerging resistance there is a steady need for new antimalarial drugs. Here, we report a new class of water soluble, non-toxic compounds, aryl-alkyl-lysines, with promising activity against the ring stage of Plasmodium falciparum . The optimal compound perturbed the plasma membrane potential and the digestive vacuole of parasites. In the murine model of malaria ( Plasmodium berghei ANKA) the compound was able to increase the survival of mice by at least 5 days by an intra-peritoneal route. Further, the compounds showed no apparent toxicity to mice at the concentration tested.